Evidências científicas como base das políticas públicas para a conservação da biodiversidade no Brasil - Gemael, Manoela Karam (2016)
One of the aims of Ecology is to aid policy makers through the development of testable predictions of relevance to society. However, published data shows there is a gap between scientific knowledge and the development and management of conservation actions; public policies for biodiversity conservation seem to lack scientific evidence to support it. Our hypothesis to explain this gap in Brazil is that academic outcomes do not outreach policy makers and it is restricted to science borders. We conducted online surveys with conservation researchers (n=24) and policy makers directly working with environment and sustainability issues (politicians, n=28, and environmental managers, n=37) to evaluate their access to scientific literature related to biodiversity conservation. We also mapped scientific literature about conservation. Our results show that Brazilian politicians and scientists do not share the same priorities concerns for conservation. Besides, our study confirms that the widely known gap between science and practice in conservation management also occurs in Brazil. Time available to read, technical language and papers published in English are pointed as the main barriers by the interviewed politicians who do not read scientific literature about conservation. Only 6% of policy makers interviewed feel very well informed about biodiversity conservation issues. Therefore, the results confirm the hypothesis that scientific knowledge does not support the development of public policies for conservation in Brazil. We consider both scientists and policy makers responsible to improve communication between their institutions. On one hand, researchers need to know in advance practitioners´ needs. On the other hand, policy makers need scientific evidences to be available in accessible language and up to date. Therefore, we recommend investments in (i) teaching science communication among young scientists, (ii) the development of science communication departments in universities, funding agencies, media vehicles, but, mostly, in all governmental levels by the institution of chief-scientists as policy and management advisors, (iii) in science education programs, (iv) on the engagement of all stakeholders related to conservation management on public policies development, (v) in evidence-based conservation tools, such as summaries of scientific evidences from literature. Future studies concerning the gap between science and conservation management in Brazil should identify practitioners’ current needs to contrast it against agencies’ funding programs for conservation studies, in order to understand current financial priorities.